The Effect of the Montessori Method Aided by Picture Media on Beginning Reading Ability (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2022)
The purpose of this study was to determine the effect of the Montessori method with the aid of picture media on the ability to read early. This study uses quasi-experimental design research in the form of a non-equivalent control group design. The population is all second-grade students of SD Inpres Tmannyeleng, Barombong District, Gowa Regency for the 2021/2022 academic year. The sampling technique used purposive sampling, with a sample of 28 students in the experimental class and 27 students in the control class. The data analysis technique in this study used the paired sample t-test. The results showed that there was a significant effect of the application of the Montessori method with the aid of picture media on the early reading ability.